An analytical model for the progressive failure prediction of reinforced thermoplastic pipes under axial compression. Issue 6 (25th March 2021) - Liu, Wencheng; Wang, Shuqing; Bu, Jiarun; Ding, Xindong
Abstract: An analytical model is presented to predict the progressive failure of reinforced thermoplastic pipes (RTPs) under axial compression, in which the existing homogenization method and a nonlinear stiffness degradation model are combined to predict the continuum damage mechanical response in an iterative and cyclic way. As the homogenization method ignores the effect of the cross‐sectional curvature on the damage sequence, a stress correction factor is defined to consider this effect. Once corrected stresses satisfy Hashin‐Yeh failure criteria, the nonlinear stiffness degradation model is adopted to update the constitutive relationship established by the homogenization method. The proposed model is capable of identifying the damage location and failure mode, analyzing damage accumulation and predicting the ultimate compression. Meanwhile, ABAQUS Explicit quasi‐static analyses calling a user‐defined subroutine were conducted to capture the progressive failure mechanisms in 3D composites and verify the proposed model. The proposed model was found to give accurate prediction on the elastic stiffness, first ply failure, the damaged stiffness, the ultimate compression, and stress distributions. Furthermore, the effects of fiber's winding angles and the thickness‐radius ratios have been discussed, which illustrate that tensile failure mode would appear even when RTPs are under axial compression. Abstract : An analytical model is presented to predict the progressive failure of RTPs under axial compression, in which the existing homogenization method and a nonlinear stiffness degradation model are combined to predict the continuum damage mechanical response in an iterative and cyclic way. It is capable of identifying the damage location, predicting failure mode, and analyzing damage accumulation.